A fiber-optic nanoplasmonic hydrogen sensor via pattern-transfer of nanofabricated PdAu alloy nanostructures. Issue 44 (6th November 2018) - Nugroho, Ferry Anggoro Ardy; Eklund, Robin; Nilsson, Sara; Langhammer, Christoph
Abstract : We demonstrate the transfer of arrays of nanofabricated noble metal and alloy nanostructures obtained by high-temperature annealing on a flat parent support onto optical fibers, to create a fiberoptic hysteresis-free nanoplasmonic hydrogen sensor. Abstract : We demonstrate the transfer of arrays of nanofabricated noble metal and alloy nanostructures obtained by high-temperature annealing on a flat parent support onto optical fibers, to create a hysteresis-free fiber optic nanoplasmonic hydrogen sensor. This work enables the integration of complex nanofabricated structures and their arrangements in tailored arrays with fiber optics to realize optical sensors, which will find application in a wide range of disciplines.